Junior doctors' mental health and coronavirus disease safety concerns - Alexandra Bartholomew; Samineh Sanatkar; Isabelle Counson; Samuel B. Harvey (Elsevier, 2022)
Abstract Objective: This article aims to assess whether caring for COVID‐19 patients impacted junior doctors' COVID‐19‐related anxieties, general anxiety and depression, and the relative impact of depression, general anxiety and specific COVID‐19 anxiety on work and social functioning during the COVID‐19 pandemic in 2020. Methods: Recruitment occurred between June and August 2020 in New South Wales, Australia. Demographic information, symptoms of depression (PHQ‐9), generalised anxiety (GAD‐7), and COVID‐19‐related anxieties around infections, help‐seeking behaviours, and work and social functioning (WSAS) were collected. Results: About one third (n=73, 33%) had cared for a patient with overt or covert COVID‐19 in the previous month. However, the extent of COVID‐19‐related anxiety symptoms was largely unrelated to caring for COVID‐19 patients. Instead, the presence of other COVID‐19 concerns and gender predicted variations in COVID‐19 concerns for one's own safety and the safety of loved ones. Conclusion: COVID‐19 anxiety symptoms were largely unrelated to caring for COVID‐19 patients, while COVID‐19‐related anxiety around the safety of family and friends added to impaired functioning in addition to the established impact of depression and general anxiety. Implications for public health: Provided the replicability of these findings, this research highlights the importance of addressing pandemic‐related anxieties in junior doctor populations.